THE USE OF ICT IN GEOGRAPHY LESSONS ON EXAMPLE OF THE TESTING PROGRAMS FOR STUDENTS' KNOWLEDGE EXAMINING - Olena P. Herashchenko (Інформаційні технології і засоби навчання, 2014)
The material gathered and analyzed in the paper is on the computer testing programs such as Assistent, MyTestX, easy Quizzy, Ayren, Master Test and others that may be used by teachers during the study of school course of "Geography" for the modernization of the modern educational process. The analysis of the possibilities of computer testing programs has showed that they can be applied on the geography lessons both for the current testing of student’s knowledge, and for the content checking and for preparation of the students for the state final attestation and external independent assessment.